A phase IB dose-escalation study of the safety and pharmacokinetics of pictilisib in combination with either paclitaxel and carboplatin (with or without bevacizumab) or pemetrexed and cisplatin (with or without bevacizumab) in patients with advanced non–small cell lung cancer. (November 2017) - Soria, Jean-Charles; Adjei, Alex A.; Bahleda, Rastilav; Besse, Benjamin; Ferte, Charles; Planchard, David; Zhou, Jing; Ware, Joseph; Morrissey, Kari; Shankar, Geetha; Lin, Wei; Schutzman, Jennifer L.; et al.
Abstract: Aim: The phosphatidylinositol 3-kinase (PI3K) pathway is a potential therapeutic target in non–small cell lung cancer (NSCLC). This study aimed to evaluate the pan-PI3K inhibitor pictilisib in combination with first-line treatment regimens that were the standard of care at the time of study, in patients with NSCLC. Patients and methods: A 3 + 3 dose-escalation study was performed using a starting daily dose of 60 mg pictilisib on days 1–14 of a 21-day cycle. Depending on bevacizumab eligibility and NSCLC histology, patients also received either paclitaxel + carboplatin or pemetrexed + cisplatin, ± bevacizumab every 3 weeks. The primary objectives of the study were to assess safety and tolerability and to identify dose-limiting toxicities (DLTs), the maximum tolerated dose (MTD) and a recommended phase II dose (RP2D), for each combination. Results: All 66 treated patients experienced at least one adverse event (AE). Grade ≥III AEs, serious AEs and deaths occurred in 57 (86.4%), 56 (84.8%) and 9 (13.6%) patients, respectively. Three patients reported DLTs across the four arms of the study. The MTD was not reached in any arm and the RP2D of pictilisib was determined to be 330 mg (capsules) or 340 mg (tablets) on a '14 days on, 7 days off' schedule. The best confirmed response was partial response in 29 (43.9%) patients and stable disease in 20 (30.9%) patients. Conclusion: Combining pictilisib with various standard-of-care first-line treatment regimens is feasible from a safety perspective in patients with NSCLC, and encouraging preliminary anti-tumour activity was observed. Highlights: Pictilisib is a potent class I pan-PI3K inhibitor. The pictilisib combination treatments were feasible from a safety perspective. No drug–drug interactions were observed in the combination treatment regimens. Encouraging preliminary anti-tumour activity was observed.